Inhibition of platelet activation alleviates diabetes-associated cognitive dysfunction via attenuating blood-brain barrier injury - Fuxing Xu; Juan Hu; Xuying Li; Lan Yang; Shiqiu Jiang; Tao Jiang; Bo Cheng; Hailiang Du; Ruiduo Wang; Yingying Deng; Wei Gao; Yansong Li; et al. (Brain Research Bulletin)
Cognitive dysfunction has become the second leading cause of death among the diabetic patients. In pre-diabetic stage, blood-brain barrier (BBB) injury occurs and induced the microvascular complications of diabetes, especially, diabetes-associated cognitive dysfunction (DACD). Endothelial cells are the major component of BBB, on which the increased expression of CD40 could mediate BBB dysfunction in diabetics. Since platelets play an important role in regulating endothelial cell barrier function and over 95 % of the circulating soluble CD40 ligand (sCD40L) is derived from activated platelets, we speculated that the release of CD40L from activated platelets induced by diabetes was the key mechanism that aggravated BBB injury and leaded to DACD. We performed inhibition of platelet activation on diabetic and non-diabetic mice, with or without cilostazol treatment, and then compared cognitive function, platelet activation, BBB structure and permeability. In vitro, mouse brain microvascular endothelial cell line (b.End3) were exposed to CD40L for 24 h at 5.5 mM or 30 mM glucose media after silencing CD40 and HIF1α or not to investigate the effects of CD40 on BBB disruption and the underlying molecular pathways. Inhibition of platelet activation improved cognitive behaviors in diabetic mice, accompanied with reduced BBB permeability, increased tight junction proteins, balanced Aβ transporters, as well as attenuated Aβ deposition and hippocampal neurons damage. In vitro, CD40L increased HIF1α, diminished tight junction proteins and dysregulated Aβ transporters in b.End3 cells, which could be restored by CD40 siRNA and HIF1α siRNA. Hence, inhibition of platelet activation ameliorates DACD via alleviating BBB injury, which involving the regulation of CD40L-CD40-HIF1α signaling pathway. Our study may demonstrate a potential therapeutic target for the treatment of DACD.